The Effect of Education and Length of Work on Employee Performance with Organizational Culture as an Intervening Variable in the Office Directors of PT. Plantation III Medan - Fajar Rezeki Ananda Lubis; Syaifuddin Syaifuddin; Yusniar Lubis (Jurnal Mantik, 2022)
This study aims to analyze the effect of education on organizational culture, the effect of length of service on organizational culture, the effect of education on employee performance, the effect of length of service on employee performance, the influence of organizational culture on employee performance, the indirect effect of education on employee performance through organizational culture and the indirect effect of length of service on employee performance through organizational culture at the Office of the Board of Directors of PT. Plantation III Medan. The population in this study were all employees of the Office of the Board of Directors of PT. Plantation III Medan totaling 75 people. Based on the Slovin formula, a sample of 43 people was obtained where the sampling technique used simple random sampling. The variables used in this study are independent variables and dependent variables. In this study the independent variables were education (X1) and length of work (X2). The dependent variable is employee performance (Y), while the intervening variable is organizational culture (Z). Data analysis used multiple linear regression test and path analysis. The results showed that education and length of work had a significant effect on organizational culture. Education and length of work have a significant effect on employee performance, while organizational culture has no significant effect on employee performance. Education has a significant effect on employee performance through organizational culture. Length of work has no significant effect on employee performance through organizational culture at the Office of the Board of Directors of PT.